UJI AKTIVITAS ANTIOKSIDAN DAN PENETAPAN KADAR FENOLAT TOTAL FRAKSI AIR DAUN KETAPANG (Terminalia catappa L.) DENGAN METODE DPPH (2,2-diphenyl-1-picrylhydrazyl) DAN METODE FOLIN-CIOCALTEU - Aldo Sahala; C.J. Soegihardjo (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2012)
Abstract: The aqueous fraction of methanolic extract of Ketapang (Terminalia catappa L.). wasinvestigated for its DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenger activity andthe total amount of phenolic using Folin-Ciocalteu method. It was found that the aqueousfraction of methanolic extract of Ketapang tested showed significant DPPH free radicalscavenging with IC50 value 34,071 0,424 g/mL. The total phenolic amount was 5.429 0.110mg equivalent mass value of gallic acid per gram aqueous fraction of the methanolic extract ofketapang leaves.Keywords: aqueous fraction, methanolic extract, Terminalia catappa, DPPH, total phenolic.